Ankylosing spondyloarthritis in the rheumatology practice of Karelia - Irina Mikhailovna Marusenko; A A Brazhnik; N N Vezikova; O A Vaskova (Современная ревматология)
The paper describes the pathological aspects of an inflammatory process in ankylosing spondyloarthritis (AS), the role of muscle spasm in maintaining the intensity of pain syndrome and stiffness, the need for the early diagnosis of AS, and the significance of the early use of nonster-oidal anti-inflammatory drugs in these patients. The results of clinical trials and the authorsX data demonstrate the high efficacy and good tolerance of nimesulide (nise) in AS.